Examen especial a la cuenta inventarios de la empresa Loor Home Center, cantón Piñas, periodo 2020. - Vicente Romero, Cristian Eduardo (2024)
ABSTRACT: The main objective of this research study was to perform a special examination of the inventory account for the company Loor Home Center, in the Piñas canton, period 2020. This work is based on evaluating the internal control system maintained by the entity to determine the veracity and reasonableness of the accounting information. This inquiry was carried out by means of the inductive and analytical method, with a field research type. A non-experimental design was applied, quantitative approach, with a descriptive level, the population was considered to be all the accounting personnel and those responsible for the management of the company's inventories. The techniques used were: observation and interview; the data collection instruments were: internal control questionnaire, interview guide. The procedures for data interpretation are: statistical analysis and documentary analysis. It was found that the company's internal controls lacked sufficient integrity, accuracy and evaluation, and the planning of the maintenance of the physical facilities of the warehouse was inadequate, which led to damage and theft, resulting in losses. The company also lacked sufficient compliance in purchasing the products because they were simply checked on the shelf and then purchased without regard to the records in the company's system. It is recommended to perform a preliminary analysis of the accounting records and inventory records before handing them over to the supervisors to know the quantity and value of the products stored in the company for the correct reconciliation of the balances made by the finance department and management. Keywords: Special Examination, Inventories, Accounting Records, Regulations, Internal Control. Firmado electrónicamente por: MARCO ANTONIO AQUINO ROJAS Firmado electrónicamente por: MARCO ANTONIO AQUINO ROJAS Reviewed by: Marco Antonio Aquino ENGLISH PROFESSOR C.C. 1753456134